Summer Hydrodynamics as a Dual Driver of Microplastic Retention and Settling in Shallow Water Columns - Hassan Elagami; Pouyan Ahmadi; Jan H. Fleckenstein; Christoph K. Thomas; Wolfgang Babel; Marco La Capra; Sven Frei; Benjamin S. Gilfedder (Water, Air, & Soil Pollution, 2026)
In shallow lakes, wind-driven turbulence and thermally induced convection control water mixing. Together, and depending on depth, they interact with microplastic (MP) settling to determine how particles are distributed throughout the water column. To investigate these processes, two MP addition experiments were conducted in a 112 m 3 aquatic mesocosm during summer using 1–5 µm microspheres. High resolution data on MP concentrations, water velocities, wind speeds, and water and air temperatures were collected. Additionally, using OpenFOAM, a three-dimensional CFD model incorporating fluid–particle interactions was configurated to quantitatively interpret the experimental data of MP transport. The results indicated that although Stokes’ settling velocity predicted MP would take up to 182 days to reach the mesocosm bottom, MP of all sizes was detected just above the bed (3 m) within only 3 days. The vertical distribution of MP, characterized using the Péclet number (Pé, settling velocity/turbulent diffusion), increased with depth but remained < 1. In the near-surface layer (< 0.25 m), approximately 10% of MP remained in suspension by forced convection (wind-induced turbulence) and particle–fluid interactions. Free convection dominated MP transport between 0.25 and 3 m depth. Pé values < 1 indicate that, despite increasing gravitational settling with depth, free convection remains the dominant process. These results demonstrate that MP transport in shallow water columns is not governed by gravitational settling alone but is fundamentally controlled by the interplay of wind-driven turbulence and thermally induced convection. This generates depth-dependent mixing regimes and redistributes MP across the water column, increasing the likelihood of exposure to aquatic organisms at all depths.

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Subsurface Fe (II) affects concentrations of dissolved O2 in streamwater - Silvia Parra-Suarez; Romy Wild; Benjamin S. Gilfedder; Juergen Geist; Johannes A.C. Barth; Sven Frei; Stefan Peiffer (Water Research, 2025)

Seasonal dynamics of groundwater discharge: Unveiling the complex control over reservoir greenhouse gas emissions - Chang Qian; Qianqian Wang; Benjamin S. Gilfedder; Sven Frei; Jieyu Yu; Giri R. Kattel; Zhi-Guo Yu (Water Research, 2025)

Eisenrückhalt in der Lausitz: Eine räumlich differenzierte Analyse der Spree - Sven Frei; Laurin Klostermann; Benjamin Silas Gilfedder (Grundwasser, 2024)
Zusammenfassung Neben den Auswirkungen des Klimawandels gestaltet sich die Beurteilung der Effekte der Post-Bergbau-Ära auf Wasserhaushalt und Qualität der Spree in der Zukunft als anspruchsvoll. Ziel dieser Studie ist es, das komplexe Zusammenspiel zwischen Oberflächen- und Grundwasser im Kontext der Verockerungs-Problematik der Spree besser zu verstehen. Dabei werden Ergebnisse einer kontrovers diskutierten Arbeit aus dem Jahr 2018 aufgegriffen und im Zusammenhang mit aktuellen Entwicklungen verglichen. Basierend auf einer räumlich differenzierten Bilanzierung beläuft sich die Gesamtmenge des im Einzugsgebiet der Spree und ihrer Zuflüsse immobilisierten Eisens auf etwa 30 t/Tag. Neben der Spree und ihrem Einzugsgebiet (39 %) spielen insbesondere die Tagebaurestseen (24 %) sowie die Zuflüsse zur Spree mit ihren jeweiligen Einzugsgebieten (34 %) eine bedeutende Rolle beim Rückhalt von Eisen. Die räumliche Verteilung der Grundwasserzuflüsse in die Spree, quantifiziert mithilfe von Radon als natürlichem Tracer, zeigt präferenzielle Eintritte entlang der Spreewitzer Rinne, die bis zu 70 % des gesamten Zuflusses (139.800 m 3 /d) ausmachen.

Is the impact of groundwater on lake greenhouse gas dynamics underestimated? A comparative analysis of subsurface and ecological factors - Jieyu Yu; Qianqian Wang; Benjamin S. Gilfedder; Chang Qian; Yueqing Xie; Giri R. Kattel; Kai Wang; Tian Zhan; Zhi-Guo Yu (Journal of Hydrology, 2024)

Systematic CFD-based evaluation of physical factors influencing the spatiotemporal distribution patterns of microplastic particles in lakes - Pouyan Ahmadi; Franz Dichgans; Lisa Jagau; Christian Schmidt; Vadym Aizinger; Benjamin S. Gilfedder; Jan H. Fleckenstein (Science of The Total Environment, 2024)

Analytical solutions for the advection-dispersion model for radon-222 production and transport in shallow porewater profiles - Allen June Buenavista; Chuan Wang; Yueqing Xie; Benjamin Gilfedder; Sven Frei; Pere Masque; Grzegorz Skrzypek; Shawan Dogramaci; James L. McCallum (Journal of Hydrology, 2023)

Radon-222 as a groundwater discharge tracer to surface waters - Dini Adyasari; Natasha T. Dimova; Henrietta Dulai; Benjamin S. Gilfedder; Ian Cartwright; Tristan McKenzie; Peter Fuleky (Earth-Science Reviews, 2023)

Quantifying microplastic residence times in lakes using mesocosm experiments and transport modelling - Hassan Elagami; Sven Frei; Jan-Pascal Boos; Gabriele Trommer; Benjamin S. Gilfedder (Water Research, 2023)

Measurement of microplastic settling velocities and implications for residence times in thermally stratified lakes - Hassan Elagami; Pouyan Ahmadi; Jan H. Fleckenstein; Sven Frei; Martin Obst; Seema Agarwal; Benjamin S. Gilfedder (Limnology and Oceanography, 2022)
Microplastics residence times in lakes are currently poorly understood. In this work, settling experiments with pristine and biofilm‐colonized microplastic particles were combined with model calculations to evaluate settling velocities, particle distributions, and residence times in the epilimnion, metalimnion, and hypolimnion of a hypothetical stratified lake broadly based on Upper Lake Constance. Settling velocities of various biodegradable and nonbiodegradable polymers of various shapes, sizes, and biofilm colonization were measured in a settling column. The settling velocities ranged between ~ 0.30 and ~ 50 mm s −1 . Particle sizes and polymer densities were identified as primary controls on settling rates. Microplastic particles that had been exposed to a lake environment for up to 30 weeks were colonized by a range of biofilms and associated extracellular polymeric substances; surprisingly, however, the settling velocity did not vary significantly between pristine and colonized microplastic particles. Simulated microplastic residence times in the model lake varied over a wide range of time scales (10 −1 to 10 5 d) and depended mainly on the size of the particles and depth of the lake layer. Long residence times on the order of 10 5 d (for 1‐ μ m microplastic particles) imply that for small microplastic particles there is a high probability that they will be taken up at some stage by lake organisms. As the lake retention time (~ 4.5 years) is considerably shorter than the residence time of small microplastics, negligible quantities of these microplastic particles should be found in the lake sediment unless some other process increases their settling velocity.

Stellungnahme zum Kommentar von Wilfried Uhlmann und Carolin Pezenka zum Beitrag „Quantifizierung lokaler Grundwassereintritte in die Spree und deren Bedeutung für die Verockerungsproblematik in der Lausitz“ in Grundwasser 25 (3), 231–241 (2020) - Sven Frei; Benjamin Silas Gilfedder (Grundwasser, 2021)

Relevance of Iron Oxyhydroxide and Pore Water Chemistry on the Mobility of Nanoplastic Particles in Water-Saturated Porous Media Environments - Taotao Lu; Benjamin S. Gilfedder; Hao Peng; Stefan Peiffer; Georg Papastavrou; Katharina Ottermann; Sven Frei (Water, Air, & Soil Pollution, 2021)

Why productive lakes are larger mercury sedimentary sinks than oligotrophic brown water lakes - Martin Schütze; Philipp Gatz; Benjamin‐Silas Gilfedder; Harald Biester (Limnology and Oceanography, 2021)
Mercury accumulation in lake sediments is a widespread environmental problem due to the biomagnification of Hg in the aquatic food chain. Soil Hg concentrations, catchment vegetation, erosion, and lake productivity are major factors controlling the accumulation of Hg in lakes. However, their influence on the Hg mass balance in lakes with different catchment characteristics and trophic state is poorly understood. In this multilake study, we decipher the effects of catchment vegetation (coniferous vs. deciduous forest), soil Hg content, and trophic state on Hg sedimentation at six lakes in Germany. We investigated Hg concentrations in leaves, soils, and the lake's water phase. Soils under coniferous stands show slightly higher Hg concentrations than under deciduous forest. Hg concentrations in the water phase were higher in the oligotrophic brown water lakes (8.1 ± 5.6 ng L −1 vs. 3.0 ± 1.9 ng L −1 ). Lower Hg concentrations in sediment trap material indicate dilution by algae organic matter in the mesotrophic lakes (0.12–0.17 μ g g −1 vs. 0.57–0.89 μ g g −1 ). However, Hg accumulation rates in sediment traps were up to 14‐fold higher in the mesotrophic lakes (113–443 μ g m −2 yr −1 ) than in the brown water lakes (32–144 μ g m −2 yr −1 ), which could not be explained by higher Hg fluxes to the productive lakes. Hg mass balance calculation reveals that water phase Hg scavenging by algae is the major reason for the intense Hg export to the sediments of productive lakes which makes them significantly larger sedimentary sinks than oligotrophic brown water lakes.

Quantifizierung lokaler Grundwassereintritte in die Spree und deren Bedeutung für die Verockerungsproblematik in der Laustiz - Sven Frei; Fabian Wismeth; Benjamin Silas Gilfedder (Grundwasser, 2020)
Zusammenfassung Eine unbekannte, schwer zu bestimmende aber zentrale Komponente in der Verockerungs-Problematik der Spree ist der lokale Grundwasserzufluss. Als Teil dieser Studie wurden mithilfe des natürlichen Tracers Radon ( 222 Rn) die lokalen Grundwasserzuflüsse in die Spree und Kleine Spree im Lausitzer Braunkohlerevier bestimmt. Der gesamte Grundwasserzufluss, für das 20 km lange Teilstück der Kleinen Spree und den 34 km langen Abschnitt der Spree, variierte je nach Messkampagne zwischen ~3.000 und ~7.000 m 3 d −1 (Kleine Spree) sowie ~20.000 und ~38.000 m 3 d −1 (Spree). Entlang der Spreewitzer Rinne, einem vom Tagebauabraum geprägten Aquifer, wurden Flussabschnitte mit besonders hohem, präferenziellem Grundwassereintritt identifiziert (bis zu 70 % des gesamten Zustromes). Für diese Bereiche gelangen große Mengen an gelöstem Eisen aus dem Grundwasser in die Fließgewässer. Basierend auf gemessenen lokalen Eisen- und Sulfatfrachten in beiden Fließgewässern, wurde für das Einzugsgebiet die Menge an zurückgehaltenem Eisen quantifiziert. Für das gesamte untersuchte Einzugsgebiet der Spree liegt die Menge an zurückgehaltenem Eisen durch die Eisenhydroxid-Bildung bei bis zu 120 Tonnen/Tag.

Grundwasserzufluss zum Steißlinger See und Folgen für die Wasserchemie - Benjamin Gilfedder; Stefan Peiffer; Franziska Pöschke; Andrea Spirkaneder (Grundwasser, 2018)

Solar irradiance and primary productivity controlled mercury accumulation in sediments of a remote lake in the Southern Hemisphere during the past 4000 years - Harald Biester; Marta Pérez‐Rodríguez; Benjamin‐Silas Gilfedder; Antonio Martínez Cortizas; Yvonne‐Marie Hermanns (Limnology and Oceanography, 2018)
Mercury (Hg) is a toxic trace element known to highly accumulate in aquatic biota and uptake by algae is the main entry‐point into the aquatic food chain. However, the effect of changes in solar irradiance and climatic conditions on Hg uptake by algae is largely unknown. We analyzed the link between sediment Hg accumulation, cyclic changes in total solar irradiance (TSI), and related changes in lake productivity as well as climate during the past 4.5 thousand years (kyr) in sediments of a small highly productive lake in Southern Patagonia (53°S). The analyses encompass proxies for TSI (based on 10 Be), sediment geochemical composition, and lake productivity (FTIR spectra, and hydrogen‐index). The sediment record shows high concentrations of organic matter (median 70%) and strong variations in Hg accumulation rates (14–53 μg m 2 yr −1 ) which correspond to changes in aquatic productivity and TSI. Accumulation of Hg was highest during dryer periods when irradiance and lake productivity was high. During these periods, accumulation was up to fourfold higher compared to those of lower TSI, lower productivity, and wetter climatic conditions. Higher amounts of algae biomass can increase Hg scavenging by organic particles and Hg export to the sediment. To obtain mass balance, we assume that the increase in sediment Hg accumulation rates during periods of lower Hg fluxes from the catchment (drier) caused a decrease in water phase Hg and in rates of Hg evasion from the lake.